(untitled) (Journal of Comparative & International Higher Education, 2023)
The common collocation “community engagement” in the language of education abroad raises problematic and complex questions, most critically what is the nature of community in the contemporary world? Does engagement impose an expectation of untroubled involvement? In our century, technology has redefined the boundaries of community; increasing fragmentation of social structures; voluntary and forced mobilities have disrupted modes of association. A collective implication is that communities are no longer necessarily defined by proximity. For good and ill, globalization, in many ambiguous shapes, has altered the ways in which we meet and interact with each other, Seeking encounters with individuals is a more productive appraoch than seeking engagement with elusive notions of community. That approach is less likely to generate reductive stereotypes based upon assumptions that those we meet are types, representative of community identities. Instead, being open to the complexities of the individuals we encounter will teach us, and our students, to recognize that we, and they, are more than the sum of collective associations. We have not taught students to understand that communal identities may have eroded, or disintegrated through a combination of urban development, globalization, secularization, and other social dynamics. What they seek to find may belong predominantly in history, in memory and myth, in libraries, in images that have begun to fade. They may be chasing shadows.